Temporal analysis and control of the ringspot disease and mite vector of Coffee ringspot virus - Almeida, João Eduardo Melo de; Mori, Arnaldi Eiki; Pozza, Edson Ampélio; Reis, Paulo Rebelles; Figueira, Antonia dos Reis (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the population fluctuation of the mite Brevipalpus phoenicis, vector of the Coffee ringspot virus (CoRSV) – the causal agent of the coffee ringspot disease –, as well as its distribution in coffee plants, and the effect of acaricides in its control in coffee crops. The experiment was carried out at the municipality of Coromandel, in the region of Alto do Paranaíba, MG, Brazil, during two years. In the second year, the progress of the disease was evaluated, and the relationship between the mite population and disease incidence was determined. Ringspot disease and mites were detected throughout the year, with larger populations and disease incidence in the months with lower rainfall and mild temperatures. Pearson analyses showed negative correlation between the climatic parameters and the mite population. In the analysis of the disease incidence in different periods, a positive correlation was found among the first and subsequent evaluations. Regarding spatial distribution, mite presence was observed in the whole plant; however, leaves are preferred by the adults, whereas the fruit are preferred for oviposition. The acaricides are effective in keeping the mite population at low levels, with consequent reduction of disease incidence.